Lekcja religii – odpowiedzialna praca na rzecz polskiej szkoły i Kościoła - Tomasik, Piotr (Studia Pastoralne, 2026)
The article refers to the concept of force in Poland lessons of religion, which is neither catechesis, although the work of catechesis in part, or religious studies lesson, though knowledge about religion provides. It tries to answer the following questions: What are the basic determinants of the concept of school religion classes? What is the concept of school religion classes in Poland? What are the opportunities and threats of this concept of religion classes?